Single-layer performance of sugarcane bagasse- and rubber tire dust microwave absorber in narrow band frequency of 3.85 GHz to 8.2 GHz - L. Zahid; M. Jusoh; N. H. Ghazali; Sabapathy Sabapathy; M. Mustapa; A. K Rahman (Institute of Advanced Engineering and Science, 2019)
In this paper, the single and flat layer of microwave absorber has been fabricated with different weight percentage of sugarcane bagasse (SCB) and rubber tire dust (RTD). The dielectric properties and wave propagation have been investigated in this work. There are two different designs in developing this layer of microwave absorber. In this work, the targeted frequency is within 3.85 GHz to 8.2 GHz. The preference was based on the fact that our goal was to achieve minimum backward reflections, and the sugarcane bagasse material, with its low dielectric constant, high loss factor, large attenuation per unit length, and ease of fabrication, provided a better opportunity to achieve that goal which is better than -10dB (90 % of absorption).